Kebijakan dan Pengambilan Keputusan Penyediaan Akomodasi yang Layak dalam Implementasi Pendidikan Inklusif - Nihan Kristiyani; Muhammad Amir Masruhim; Ady Setiawan (Manajemen Pendidikan Program Doktor, 2025)
This study aims to find out the Policy and Decision Making of the Provision of Decent Accommodation in the Implementation of Inclusive Education. Asta Cita Pendidikan Indonesia is said to focus on improving the quality of human resources, equitable distribution of inclusive quality education. The research method used in this study is qualitative with a descriptive method, and data was obtained from literature studies, observations and interviews. The results of this study show that the Samarinda City Government provides several derivative regulations that are relevant to the implementation of inclusive education, carries out preparations for the provision of educators and education personnel through the implementation of teacher training and technical guidance activities, establishes Disability Service Units, and builds Inclusive Resource Spaces in regular/public schools, as well as forming Special Supervisory Teacher Working Groups (KKGPK). A total of 269 educators and education staff have participated in inclusive education training and technical guidance from 80 regular/public schools. The provision of the Budget for the Disability Service Unit is also provided with no less than Rp.300 million per year. This implementation is carried out as a fulfillment of the right of every citizen to obtain education and is non-discriminatory by upholding human rights and the plurality of the nation